2021
DOI: 10.18203/2349-2902.isj20211330
|View full text |Cite
|
Sign up to set email alerts
|

Free radial artery forearm flap reconstruction of forehead defect in a 2-year-old child

Abstract: Reconstruction of soft tissue defect with exposed bone over the forehead is a technical challenge in pediatric population. The options vary from skin grafting, local flaps to complex microvascular tissue transfer. The local flaps leave unsightly scar in the neighboring area and may violate the hair bearing scalp, hair line and the direction of hair. Skin grafting requires a vascular bed for its take and the aesthetic appearance is inferior. The tissue expansion in an acute stage may not be an option. Here we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…7 Later on, various authors reported and observed the use of free flap in small children to be possible and safe. 8 Yazar et al analyzed the safety and reliability of microsurgical free tissue transfer in pediatric head and neck reconstruction in 72 cases and found a success rate of 98.6%, which is comparable to various studies in adults. 9 Vessel anastomosis in pediatric patients is challenging, but due to improved microsurgical skills and the use of microscope, it has the same patency as in adults.…”
Section: Discussionmentioning
confidence: 61%
“…7 Later on, various authors reported and observed the use of free flap in small children to be possible and safe. 8 Yazar et al analyzed the safety and reliability of microsurgical free tissue transfer in pediatric head and neck reconstruction in 72 cases and found a success rate of 98.6%, which is comparable to various studies in adults. 9 Vessel anastomosis in pediatric patients is challenging, but due to improved microsurgical skills and the use of microscope, it has the same patency as in adults.…”
Section: Discussionmentioning
confidence: 61%